Strategi Komunikasi dalam Pembinaan Akhlak Santri Madrasah Diniah Imaaniyyah Bedingin Sambit Ponorogo - Tamrin Fathoni (Journal of Communication Studies, 2022)
Communication has a strategic place in the world of education. Education is communication. it means that in the process involved two components consisting of the teacher as a communicator and students as communicants. The purpose of this study was to find out how the form of a teacher's communication strategy to a student at the Madrasah Diniyah imaniyah bedingin Sambit Ponorogo institution in the midst of the conditions of the millennial era of morality and karimah of a santri starting to be undermined. This study uses a descriptive qualitative approach with data collection techniques through interviews, documentation, and observation. The results of this study were 1) Materials for the moral development of students at Madrasah Diniyah Imaniah bedingin Sambit Ponorogo in the form of a series of materials delivered by a teacher to students. The subjects in Madrasah Diniyah Imaniah are so complete in accordance with the needs of students, especially in moral development. 2) The method of fostering the morals of students at Madrasah Diniyah Imaniyyah Bedingin Sambit Ponorogo. Some of the learning methods applied in Madrasah Diniyah Imaniyyah are lecture and question and answer methods. With these two methods, it is deemed sufficient according to the needs of students in receiving the knowledge given by the teacher.